Live Poultry Exposure and Public Response to Influenza A(H7N9) in Urban and Rural China during Two Epidemic Waves in 2013-2014 - Wu, Peng; Wang, Liping; Cowling, Benjamin J.; Yu, Jianxing; Fang, Vicky J.; Li, Fu; Zeng, Lingjia; Wu, Joseph T.; Li, Zhongjie; Leung, Gabriel M.; Yu, Hongjie (PloS one, 2015)
The novel influenza A(H7N9) virus has caused 2013 spring and 2013-2014 winter waves of human infections since its first emergence in China in March 2013. Exposure to live poultry is a risk factor for H7N9 infection. Public psychobehavioral responses often change during progression of an epidemic. We conducted population-based surveys in southern China to examine human exposure to live poultry, and population psychological response and behavioral changes in the two waves. In Guangzhou, an urban area of Guangdong province, we collected data using telephone surveys with random digit dialing in May-June 2013 and again in December 2013 to January 2014. In Zijin county, a rural area of the same province, we used door-to-door surveys under a stratified sampling design in July 2013 and again in December 2013 to January 2014. All responses were weighted by age and sex to the respective adult populations. Around half of the urban respondents (53.8%) reported having visited LPMs in the previous year in the first survey, around double that reported in the second survey (27.7%). In the rural surveys, around half of the participants reported raising backyard poultry in the past year in the first survey, increasing to 83.2% participants in the second survey. One third of urban subjects supported the permanent closure of LPMs in the first and second surveys, and factors associated with support for closure included female sex, higher level of worry towards H7N9, and worry induced by a hypothetical influenza-like illness. Our study indicated high human exposure to live poultry and low support for permanent closure of markets in both urban and rural residents regardless of increased worry during the epidemic.